Three-step synthetic procedure to prepare dolutegravir, cabotegravir, and bictegravir - Xianheng Wang; Song Chen; Hanqi Cui; Yuqi He; Changkuo Zhao (Green Chemistry Letters and Reviews, 2022)
Dolutegravir, cabotegravir, and bictegravir are three integrase inhibitors, which were used for HIV-1 in the clinic. In this paper, a continuous three-step synthetic strategy was developed to prepare dolutegravir, cabotegravir, and bictegravir in a better yield, compared to the initial step-by-step procedure. Different solvents, temperature, and times were optimized. In the course of industrial production of active pharmaceutical ingredient (API), this three-step synthetic protocol has several advantages, including low cost, time-saving, and better yield. This process was successfully scaled up to tens of grams.